O riso e o sorriso nos processos de socialização e construção identitária - Alexandre Guilherme de Araujo Compart (2009)
This study intends to comprehend the placement of the smile and the laughter in the socialization and identity construction processes, observing the works of assimilation, selection and sign hierarchization operated by individual perception. It also seeks to enter the chain of signification and generate interpretative hypothesis, taking individual reactions as tools to verify which is the relation of need in which they are located with the formulated structures that stimulated them. This analysis is leaded both by the consideration of the smile as spontaneous reaction, given the constantly constructed socialization, and the apprehension of the intention of individuals on its contextual and strategic levels. In both cases, it is highlighted not only the structure/content of the communication of the smiling reaction, but also the performative aspects that are likely to be located in space and in time.